Mergers and acquisitions in OIC countries: the role of strategic similarity in bank performance - Raudhatun Nisa; Sugiyarti Fatma Laela; Mohamed Eskandar Shah (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - This research aims to evaluate the impact of strategic similarity on M&A performance in banking within OIC countries. The study investigates how strategic alignment influences M&A outcomes and explores the role of cultural fit, cross-border factors, and capital adequacy in shaping post-merger success.Method - A quantitative approach is used in this study, using secondary data from annual reports of banking institutions in OIC member countries that experienced mergers and acquisitions from 2013 to 2022. This study uses 38 M&A transaction data obtained from Bank Focus. The hypothesis is tested using a partial least squares structural equation model.Result - The finding reveals that the strategic similarity factor could not explain the success of M&A performance for both Islamic and conventional banks. Cultural misalignment and cross-border regulatory issues are key factors affecting post-merger success. The one-year observation period was too short, but capital adequacy was found to influence performance significantly.Implication - Theoretically, models of M&A success should include cultural and regulatory dimensions and consider a longer-term view. Managers should prioritise cultural integration, address regulatory challenges, and align capital adequacy strategies to improve post-merger outcomes and resilience.Originality - This research discussed the factors determining successful M&A performance in banks in OIC countries. The findings can be used to develop insights into mergers and acquisitions in the banking sector.